Use of the Vula App to refer patients in the West Coast District: A descriptive exploratory qualitative study - Louwrens Steyn; Robert J. Mash; Gavin Hendricks (South African Family Practice)
Background: Referral systems play a pivotal role in coordination and quality of care and should be evaluated for their utility. The Vula App is used by various disciplines and hospitals in South Africa to refer patients. The aim was to explore the perceptions of medical practitioners regarding the use of the Vula App in the West Coast District.